Patterned silk film scaffolds for aligned lamellar bone tissue engineering - Tien, Lee W. (2012)
Various porous biomaterial scaffolds have been utilized for bone tissue engineering; however, they are often limited in their ability to replicate the structural hierarchy and mechanics of native cortical bone. In this study, the alignment and osteogenic differentiation of human mesenchymal stem cells (MSCs) on patterned silk films (PF) was investigated as a bottom-up, biomimetic approach toward engineering cortical bone lamellae. Screening films cast with nine different micro and nano scale groove patterns showed that cellular alignment was mediated by an interplay between the width and depth of the patterns. MSCs were differentiated in osteogenic medium for four weeks on the PF that induced the highest degree of alignment, while flat films (FF) served as controls. Gene expression analysis and calcium quantification indicated that the PF supported osteogenic differentiation while also inducing robust lamellar alignment of cells and matrix deposition. A secondary alignment effect was noted on the PF where a new layer of aligned cells grew over the first layer, but rotated obliquely to the underlying pattern direction and first layer orientation. This layering and rotation of the aligned MSCs resembled the characteristic structural organization observed in native lamellar bone. The ability to control multilayered lamellar structural hierarchy from the interplay between a patterned 2D surface and cells suggests intriguing options for future biomaterial scaffolds designed to mimic native tissue structures.